2022
DOI: 10.26559/mersinsbd.985019
|View full text |Cite
|
Sign up to set email alerts
|

Şark çıbanı vakalarında bilgi ve farkındalık düzeyini artırmaya yönelik müdahale çalışması: Şanlıurfa örneği

Abstract: Aim: In this study, it was aimed to determine whether there was a change in the level of knowledge about the disease without education during the treatment and the effect of health education on the level of knowledge of the patients about the disease in patients with cutaneous leishmaniasis. Method: The research was of intervention type and was carried out in Şanlıurfa Cutaneous Leishmanias Diagnosis and Treatment Center. The study was completed with a total of 102 people, 51 of whom were in the intervention g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
1
0
1
Order By: Relevance
“…In the research, awareness, and knowledge levels were discussed separately according to the diseases. In these studies, it was found that the knowledge and awareness levels were not sufficient [9][10][11][12][13]. Relevant disease awareness practices regarding public knowledge can help control the disease.…”
Section: Introductionmentioning
confidence: 99%
“…In the research, awareness, and knowledge levels were discussed separately according to the diseases. In these studies, it was found that the knowledge and awareness levels were not sufficient [9][10][11][12][13]. Relevant disease awareness practices regarding public knowledge can help control the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Bu durum da hastalığın kontrolünü güçleştirmektedir. 6 Hastaların tedavi arama davranışını ve sağlık kuruluşlarına başvuru sürelerini belirleyen birçok sosyal ve kültürel faktör bulunmakta olup, sağlık davranışlarıyla birlikte tedavi hizmetleri konusundaki bilgi ve tutumları önde gelen faktörlerdendir. 7 Kişilerin sağlık okuryazarlığı (SOY) düzeylerinin artışı, hastalıkları konusunda öz sorumluluk sahibi olmalarına ve tedavi arama çabalarına katkı sağlayacaktır.…”
Section: Introductionunclassified